Anticancer Mechanisms of Salinomycin in Breast Cancer and Its Clinical Applications - Wang, Hui; Zhang, Hongyi; Zhu, Yihao; Wu, Zhonghang; Cui, Chunhong; Cai, Fengfeng (Frontiers in Oncology, 2021)
Breast cancer (BC) is the most frequent cancer among women worldwide and is the leading cause of cancer-related deaths in women. Cancer cells with stem-like features and tumor-initiating potential contribute to drug resistance, tumor recurrence, and metastases. To achieve better clinical outcomes, it is crucial to eradicate both bulk BC cells and breast cancer stem cells (BCSCs). Salinomycin, a monocarboxylic polyether antibiotic isolated from Streptomyces albus, is able to precisely kill cancer stem cells (CSCs), particularly BCSCs, by various mechanisms, including apoptosis, autophagy, and necrosis. There is increasing evidence that salinomycin can inhibit cell proliferation, invasion, and migration in BC, and reverse the immune-inhibitory microenvironment to prevent tumor growth and metastasis. Therefore, salinomycin is a promising therapeutic drug for BC. In this review, we summarize established mechanisms by which salinomycin protects against BC and discuss its future clinical applications.